Structural, elastic, electronic, and magnetic properties of MnNbZ (Z = As, Sb) and FeNbZ (Z = Sn, Pb) semi-Heusler alloys - Dinesh Kumar Yadav; Shalika Ram Bhandari; Gopi Chandra Kaphle (Materials Research Express, 2020)
The study of structural, electronic, magnetic, and elastic properties of a new series of semi-Heusler alloys MnNbZ (Z = As, Sb) and FeNbZ (Z = Sn, Pb) has been performed by density functional theory. The magnetic phase and hence the structural stability of the alloys were considered wherein the ferromagnetic state is found to be stable. The half-metallic states are observed from the density of states and band structure calculations. The total magnetic moments found for all studied compounds are 1 μ _B /f.u., which obey the Slater-Pauling rule for semi-Heusler with ferromagnetic behavior. The calculated cohesive and formation energies confirmed the thermodynamical stability and elastic constant C _ij confirmed the mechanical stability. Among the four systems, MnNbAs is found to have the highest ductility (i.e., non-directional metallic bonding) while the remaining systems are found to be brittle in nature (i.e., directional covalent bonding). These properties confirmed that among others, MnNbAs is one of the novel candidate for spintronic device applications.